Stature Estimation in Egyptian Primary School Children from Giza Governorate (Indian Journal of Forensic Medicine & Toxicology, 2020)
Stature is one of the used parameters for identification in forensic anthropology. This study aimed to developa formula to estimate the stature of children using anthropometric measurements. Ten anthropometricmeasurements were measured for 350 students randomly selected from two primary schools. The arm spanexceeds height at old ages and the majority of measurements were higher in girls. A strong correlation wasfound for stature and majority of measurements.